FXR1-related congenital myopathy: expansion of the clinical and genetic spectrum. Issue 11 (7th April 2022) - Mroczek, Magdalena; Longman, Cheryl; Farrugia, Maria Elena; Kapetanovic Garcia, Solange; Ardicli, Didem; Topaloglu, Haluk; Hernández-Laín, Aurelio; Orhan, Diclehan; Alikasifoglu, Mehmet; Duff, Jennifer; Specht, Sabine; Nowak, Kristen; et al.
Abstract : Background: Biallelic pathogenic variants in FXR1 have recently been associated with two congenital myopathy phenotypes: a severe form associated with hypotonia, long bone fractures, respiratory insufficiency and infantile death, and a milder form characterised by proximal muscle weakness with survival into adulthood. Objective: We report eight patients from four unrelated families with biallelic pathogenic variants in exon 15 of FXR1 . Methods: Whole exome sequencing was used to detect variants in FXR1 . Results: Common clinical features were noted for all patients, which included proximal myopathy, normal serum creatine kinase levels and diffuse muscle atrophy with relative preservation of the quadriceps femoris muscle on muscle imaging. Additionally, some patients with FXR1 -related myopathy had respiratory involvement and required bilevel positive airway pressure support. Muscle biopsy showed multi-minicores and type I fibre predominance with internalised nuclei. Conclusion: FXR1 -related congenital myopathy is an emerging entity that is clinically recognisable. Phenotypic variability associated with variants in FXR1 can result from differences in variant location and type and is also observed between patients homozygous for the same variant, rendering specific genotype–phenotype correlations difficult. Our work broadens the phenotypic spectrum of FXR1 -related congenital myopathy.